A review of fatigue test data on weld toe grinding and weld profiling. (April 2021) - Braun, Moritz; Wang, Xiru
Graphical abstract: Highlights: An assessment of 445 fatigue test results from 33 studies on weld toe grinding. With yield strength between 235 MPa and 1100 MPa. A S–N curve slope of m = 4 and a 2 FAT class improvement is recommended. Abstract: The aim of this paper is to investigate the effects of weld toe grinding and weld profiling on the fatigue strength of welded joints and the main influencing factors. Thus, experimental test results of welds improved by different grinding techniques are reviewed. In total, 445 small- and full-scale fatigue test results of various weld types and steel grades with yield strengths up to 1100 MPa are analysed. The obtained improvements of two FAT classes correspond well with current guidelines; however, a new S–N curve slope of m = 4 is recommended—in line with proposals for other weld geometry improvement techniques.